Management of Islamic Boarding Schools In Deli Serdang Regency (A Multisite Study of Darul Arafah and Fahmussalam Al Aziziyah Islamic Boarding Schools In Deli Serdang) - Tongat, Tongat; Nur Nasution , Wahyuddin; Siahaan, Amiruddin (Edukasi Islami: Jurnal Pendidikan Islam, 2023)
This study examines the planning, orientation, grouping, discipline development, special services, recording, evaluation, graduation, and alumni of Darul Arafah and Fahmussalam Al Aziziyah Islamic Boarding Schools. The research uses a qualitative multisite method, using interviews, observations, and studies to collect data. The study found that planning students is done on end-year teachings, orientation involves handovers between parents, and grouping involves separate entry for female and new students. Guidance discipline is provided through mudabbir, OSP, language development, coaching, prayer poles, and taxi. Special services are available for handling super-active students, such as smoking, dropping out, and dating. Recording is done for report cards and diplomas, and evaluation is conducted in each semester using oral, written, mid-semester, and final semester exams. The study also found that Darul Arafah Islamic boarding schools have strong alumni networks, with many existing graduates and alumni spread throughout Indonesia. The study emphasizes the importance of ensuring the validity of data findings and authenticity in research.